2005
DOI: 10.1359/jbmr.050202
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Vitamin B12 Status Relate to Bone Turnover Markers, Broadband Ultrasound Attenuation, and Fractures in Healthy Elderly People

Abstract: Hyperhomocysteinemia may contribute to the development of osteoporosis. The relationship of Hcy and vitamin B 12 with bone turnover markers, BUA, and fracture incidence was studied in 1267 subjects of the Longitudinal Aging Study Amsterdam. High Hcy and low vitamin B 12 concentrations were significantly associated with low BUA, high markers of bone turnover, and increased fracture risk.Introduction: Hyperhomocysteinemia may contribute to the development of osteoporosis. Vitamin B 12 is closely correlated to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
127
3
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(146 citation statements)
references
References 50 publications
7
127
3
4
Order By: Relevance
“…To exclude the possibility that substantial baseline levels of B 12 were present in the culture medium, a quantitative measurement of B 12 levels was carried out. Baseline levels were lower than 15 pM, which is far below the B 12 deficiency level of 200 pM [13]. Culturing hMSCs in osteogenic differentiation medium resulted in a homogeneous population of ALP-positive cells after 9 days of culture, as visualized by cytochemical staining for ALP (Fig.…”
Section: Vitamin B 12 Deficiency Does Not Affect Osteoblast Differentmentioning
confidence: 88%
See 1 more Smart Citation
“…To exclude the possibility that substantial baseline levels of B 12 were present in the culture medium, a quantitative measurement of B 12 levels was carried out. Baseline levels were lower than 15 pM, which is far below the B 12 deficiency level of 200 pM [13]. Culturing hMSCs in osteogenic differentiation medium resulted in a homogeneous population of ALP-positive cells after 9 days of culture, as visualized by cytochemical staining for ALP (Fig.…”
Section: Vitamin B 12 Deficiency Does Not Affect Osteoblast Differentmentioning
confidence: 88%
“…Several studies have reported that low plasma B 12 levels are associated with reduced bone quality [5,8,9,13,14], but this relation has not been observed by others [15][16][17]. More consistently, however, are the observations that increased Hcy may be a predictive factor for fracture risk [13][14][15][18][19][20][21]. Also, elevated MMA levels have been associated with osteoporosis in the elderly [14] and low bone mineral density (BMD) in adolescents [6].…”
mentioning
confidence: 99%
“…In 2004, two landmark studies performed in the Netherlands and the USA produced consistent findings in terms of the magnitude of increased risk of fracture associated with mild elevations in homocysteine (36,37) . In subsequent years, further studies from the USA, the Netherlands and Norway similarly demonstrated increases in fracture risk associated with elevated homocysteine concentrations (31)(32)(33)35) . Confirming these findings, a recent meta-analysis involving nine prospective studies and 14 863 participants reported a relative risk of 1.59 (95 % CI 1.30, 1.96) and 1.67 (95 % CI 1.17, 2.38) for all fractures and hip fractures, respectively, in those within the highest homocysteine quartile compared with the lowest (30) .…”
Section: Evidence From Observational Studiesmentioning
confidence: 95%
“…In the past decade, numerous large observational studies have provided evidence to support a role for homocysteine and/or low B-vitamin status in fracture risk (Table 1) (12,(29)(30)(31)(32)(33)(34)(35)(36)(37) . In 2004, two landmark studies performed in the Netherlands and the USA produced consistent findings in terms of the magnitude of increased risk of fracture associated with mild elevations in homocysteine (36,37) .…”
Section: Evidence From Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation